Fraud Hexagon Elements as a Determination of Fraudulent Financial Reporting in Financial Sector Services - Maryani, Neni; Natita, Rendi Kusuma; Rudiana, Rudiana; Herawati, Tuti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The goal of this study is to examine the impact of all fraud factors. Hexagon Model in order to detect fraudulent financial reporting which will form a fraudulent financial reporting based on the fraud hexagon elements. The test for determining the elements of the fraud hexagon that affect fraudulent finan-cial reporting will use the Wald Test and G Test, the likelihood ratio test using the stepwise regression and forward regression methods. Furthermore, the fea-sibility test model will be carried out. If the model formed does not pass the series of tests, there will be some improvements to the model to test the regres-sion specification error test (RESET). This is the strength of this study if we compare to previous studies. This Study shows that The Opportunity is viewed from the ineffectiveness of the supervisor, and the change of the chairman of the internal auditor influences fraudulent financial reporting. Other causes include financial target pressure, external pressure, and personal financial demands; Opportunity in terms of external auditor quality; Rationalization based on external auditor change and audit opinion; Capability that is seen from a change of directors; The amount of images of CEOs and CEO politicians demonstrates arrogance; and collusion which is reviewed from the amount of audit fee has no effect on Fraudulent Financial Reporting.